Infrared Emission Properties of Active Galactic Nuclei from Swift-BAT Hard X-Ray Survey. (19th July 2021) - Yang, Xiao-Hong
Abstract: The Swift/Burst Alert Telescope (BAT) 105-month survey detected 1632 hard X-ray sources in the 14–195 keV band, which includes 1105 active galactic nuclei (AGNs) that are unbiased against Compton-thin obscuration. We use a series of two-color diagrams to analyze the near, mid (MIR), and far-infrared properties of the Swift/BAT AGNs, based on data from the Two Micron All Sky Survey, the Wide Field Infrared Survey Explorer and the AKARI satellite. The two-color diagrams imply that a F λ ∝ λ − α power-law spectrum of α < 0 can be used to describe the 1.25–22 μ m spectra of most of the Swift/BAT AGNs and that, for some Swift/BAT AGNs, the power-law spectrum can extend to 90 μ m. Of the Swift/BAT AGNs, type-1 AGNs and QSOs have similar MIR spectral indexes ( α ) on average. Type-2 AGNs have redder MIR colors than type-1 sources on average. For 50% of type-2 Swift/BAT AGNs, their near-infrared emissions are dominated by thermal emission of the stars in host galaxies. For 83% of type-1 Swift/BAT AGNs, their near-infrared emissions may be dominated by multi-temperature thermal emissions from an optically thick accretion disk around the central black holes. The spectral index of blazars is smaller than that of other Swift/BAT AGNs, which indicates that blazars/FSRQ have flatter 4–22 μ m spectra compared to other Swift/BAT AGNs on average.